answersLogoWhite

0


Best Answer

(2a + b)(a + 3b)

User Avatar

Wiki User

โˆ™ 2012-02-21 17:25:03
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides
๐Ÿ““
See all Study Guides
โœ๏ธ
Create a Study Guide

Add your answer:

Earn +20 pts
Q: What is the answer to 2a squared plus 7ab plus 3b squared?
Write your answer...
Submit
Related questions

5a squared plus 3b squared plus 2a squared plus 4b squared?

No


2A plus 3B times 2A - 3B?

2A plus 3B times 2A - 3B = 4A2 - 9B2; this is an example of the general formula (a + b)(a - b) = a2 - b2.


3a plus 3b-2a plus 5b?

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b


Simplify 4a plus 7b plus 6a-3b-2a?

11a+7b-(3b-2a)


What is 1a plus 2a plus 3b plus 4b and what is the answer?

1a+3b 2a+4b=3a +7b


2a plus 3b - 4a plus 5b?

8b -2a


What is 3a-5b plus 6b-2a plus 3b-7b?

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b


6ab plus 9b divided by 2a plus 3?

(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b


How do you solve 2ab-3b2-3b plus 2a?

2ab - 3b2 - 3b + 2a does not have a solution, as it is not an equation.


Simplify 2a plus 3b plus 5a plus 6 plus 3b?

6+7a+6b


Factor 3ab plus a plus 3b squared plus b?

(a+b)(3b+1)


Which is a factor of 6a2 plus 5ab - 6b2?

6a2 + 5ab - 6b2 = 6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)*(3a - 2b)


What is 2a plus 3b?

2a + 3b


What is -5a plus 2b plus 3a plus b?

-2a plus 3b


Does 2a plus 3b equal 5ab?

No. 2a is one thing, 3b is another. If you add them together, they become 2a + 3b. 5ab indicates that multiplication has taken place. 5 times a times b = 5ab


Simplify the expression 2a -3 plus 4b - 2a -b -3 plus 5?

3b -1


What is 9a plus 3b-11a-4b?

9a + 3b - 11a - 4b = -2a -b


Simplify 2a -3 plus 4b - 2a -b -3 plus 5?

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1


2a -3 plus 4b - 2a -b -3 plus 5?

2a-3+4b-2a-b-3+5=3b-1


What is the verbal phrase of 2a plus 3b?

two A plus three B


What is the answer to 2a x 3b?

2a x 3b = 6ab


What is 16a plus 3b-c-5a plus 3b plus 7c plus a equals?

12a + 6b + 6c = 6(2a + b + c)


How do you factor ab plus 2a plus 3b plus 6?

(a + 3)( b + 2)


What is ab 2a 3b 6?

ab + 2a + 3b + 6


Factor 3ab - a - 3b squared plus b?

6